Hyaluronic Acid Synthesis Contributes to Tissue Damage in Systemic Lupus Erythematosus - Suarez-Fueyo, Abel; Tsokos, Maria G.; Kwok, Seung-Ki; Maeda, Kayaho; Katsuyama, Eri; Lapchak, Peter H.; Tsokos, George C. (Frontiers in Immunology, 2019)
Hyaluronic acid (HA), a component of the extracellular matrix, is the ligand for CD44 and has been implicated in the pathogenesis of kidney inflammation in patients with systemic lupus erythematosus (SLE), but its direct role and mechanism of action have not been studied. Here we show that administration of hymecromone (4-Methylumbelliferone, 4-MU), an HA synthesis inhibitor, to lupus-prone mice suppressed dramatically lupus-related pathology. Interestingly, 4-MU stopped the appearance of disease when administered prior to its onset and inhibited the progression of disease when administered after its appearance. Inhibition of HA synthesis in vivo reduced tissue damage and the number of intrarenal lymphoid cell infiltrates including double negative CD3+CD4-CD8- T cells which are known to be involved in the pathogenesis of SLE. Exposure of human peripheral blood mononuclear cells to HA in vitro increased the generation of CD3+CD4-CD8- T cells through a mechanism involving Rho-associated kinase. Our results signify the importance of the HA-rich tissue microenvironment in the activation of lymphocytes to cause tissue damage in SLE and suggest the consideration of inhibition of HA synthesis to treat patients.